The Effect of Additives on the Early Stages of Growth of Calcite Single Crystals. (18th August 2017) - Kim, Yi‐Yeoun; Freeman, Colin L.; Gong, Xiuqing; Levenstein, Mark A.; Wang, Yunwei; Kulak, Alexander; Anduix‐Canto, Clara; Lee, Phillip A.; Li, Shunbo; Chen, Li; Christenson, Hugo K.; Meldrum, Fiona C.
Abstract: As crystallization processes are often rapid, it can be difficult to monitor their growth mechanisms. In this study, we made use of the fact that crystallization proceeds more slowly in small volumes than in bulk solution to investigate the effects of the soluble additives Mg 2+ and poly(styrene sulfonate) (PSS) on the early stages of growth of calcite crystals. Using a "Crystal Hotel" microfluidic device to provide well‐defined, nanoliter volumes, we observed that calcite crystals form via an amorphous precursor phase. Surprisingly, the first calcite crystals formed are perfect rhombohedra, and the soluble additives have no influence on the morphology until the crystals reach sizes of 0.1–0.5 μm for Mg 2+ and 1–2 μm for PSS. The crystals then continue to grow to develop morphologies characteristic of these additives. These results can be rationalized by considering additive binding to kink sites, which is consistent with crystal growth by a classical mechanism.